2000
DOI: 10.1088/0031-9155/45/7/312
|View full text |Cite
|
Sign up to set email alerts
|

The saturation loss for plane parallel ionization chambers at high dose per pulse values

Abstract: The use of plane parallel ionization chambers with electron beams with high dose per pulse entails dose uncertainties due to the overestimation of the ion recombination factor, k, up to 20% if conventional dosimetric protocols are used. In this work MD-55-2 radiochromic films have been used as reference dosimeters to obtain dose to water per pulse DGAF(w) values for three Novac7 (Hitesys) electron beams of E0 = 5.8 MeV. However, the beam calibration by MD-55-2 films is time consuming and the use of plane paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 11 publications
3
50
1
Order By: Relevance
“…This calculation procedure has been considered to be appropriate once the linear dependence of 1/M and 1/V required by the Boag theory is determined to be satisfied. Some publications show that this linear dependence is not valid over a certain threshold voltage for various chambers, both plane‐parallel ( 15 , 20 23 ) and cylindrical. ( 24 , 25 ) …”
Section: Resultsmentioning
confidence: 99%
“…This calculation procedure has been considered to be appropriate once the linear dependence of 1/M and 1/V required by the Boag theory is determined to be satisfied. Some publications show that this linear dependence is not valid over a certain threshold voltage for various chambers, both plane‐parallel ( 15 , 20 23 ) and cylindrical. ( 24 , 25 ) …”
Section: Resultsmentioning
confidence: 99%
“…This fact sets a limit to the employ of ionisation chambers for the beams calibration in terms of dose per MU. In particular, due to the high density of electric charge produced in the chamber's volume per radiation pulse, the correction factor for ion recombination can be largely overestimated if the correction methods recommended by the international protocols are used 15,39,40 . For this reason, for the measure of dose to water in reference conditions, ionisation chambers cannot be employed and no published dosimetry protocol can be used.…”
Section: Dedicated Acceleratorsmentioning
confidence: 99%
“…Ionisation chambers, as previously reported, are advised against: due to the high density of electric charges produced in the volume of the chamber for each radiation pulse, in fact, the correction factor for the ion recombination 11,15,39,40 can be largely overestimated when the correction methods recommended in the international dosimetry protocols are applied. The recombination factor, moreover, may vary depending on the depth in the phantom of the point of measurement.…”
Section: Dedicated Acceleratorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the two‐voltage method has been shown to be notably inaccurate for both low electric field strength (6) and very large doses per pulse 14 , 15 . Piermattei et al, (14) for example, showed substantial error in the recombination correction estimated by the two‐voltage technique for a high dose‐per‐pulse intraoperative electron therapy accelerator. That error corresponded to a 20% difference in dose to water measured by several ion chambers, as compared to a dose‐per‐pulse independent dosimeter.…”
Section: Introductionmentioning
confidence: 99%